2019
DOI: 10.1111/jfpp.14366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical, physical, and ultrasound treatments on the shelf life of fresh‐cut quince fruit ( Cydonia oblonga Mill.)

Abstract: The study was conducted to examine the effect of chemical treatment (ascorbic acid and calcium chloride), physical treatment (water bath at 65 °C), and ultrasound (US) in ultrasonic bath for the prevention of enzymatic browning of fresh‐cut quince slices during 14 days of storage. The treated quince slices were analyzed in terms of color, polyphenol oxidase, and pectin methyl esterase activity, bioactive compounds, sensory, and microbial analysis. The results showed that US treatment inhibited (p < .05) the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…Color ( L , a *, & b * values) of each apple‐grape juice blends were examined by placing them in 35‐mm plastic dish and subjecting the samples (10 ml) to Hunter colorimeter (Model: Labsan‐XE, Hunter Associates Labs, Inc. USA). All the readings were taken in triplicates (Yildiz, Izli, & Aadil, ).…”
Section: Methodsmentioning
confidence: 99%
“…Color ( L , a *, & b * values) of each apple‐grape juice blends were examined by placing them in 35‐mm plastic dish and subjecting the samples (10 ml) to Hunter colorimeter (Model: Labsan‐XE, Hunter Associates Labs, Inc. USA). All the readings were taken in triplicates (Yildiz, Izli, & Aadil, ).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonic vibrations with the frequency of 20 to 100 kHz may lead to very quick sequences of possible compressions and expansions in a such way to a sponge effect when it is squeezed and released over and over again. Furthermore, ultrasound creates cavitation, which might be useful to eliminate firmly attached moisture (Yildiz et al, 2020). The sponge effect by HUS treatment could be the reason for the production of microscopic channels in porous food products (i.e., fruit) that reduces the diffusion boundary layers and rises the convective mass movement in the food products (De la Fuente-blanco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound studies have also found applications in isolation of bioactive compounds and processing pastes and juices in many fruits and vegetables. Recently, the technique was used to find the total phenolic content in spices like saffron (Teng et al 2019 ; Azam et al 2020 ; Yildiz et al 2020 ). Table 4 shows the application of ultrasound technologies for various food crops.…”
Section: Prevalent Food Preservation Technologiesmentioning
confidence: 99%